Anatomical Changes in Young Women with Polycystic Ovary Syndrome and First Line Treatment, A Clinical Study - Bakhtawar Mateen, Rizwana Hussain, Shahnaz Bano Memon, Arisha Sana Memon, Jawad Mumtaz Sodhar, Majid Ali Hingoro (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and objectives: The aims and objectives of current study were to provide health awareness to the young women about closed correlation among polycystic ovary syndrome and obesity which caused physio-anatomical changes with its treatment protocol. Materials and Methods Study deigned: This study was conducted from 10-11-2021to march 31-3-2022 at different medical centers of Sind Pakistan. Sample sized: 150 total women of age in between 20-30 years were selected and divided them into two different groups. In Group-C 50 normal female with regular menstrual cycle were included while in Group-A 70 female individuals with irregular menstrual cycle (polycystic ovary syndrome) were placed. On the other hand in Group-B, 30 women with polycystic ovary syndrome and obesity treated with Metformin, Clomiphene and Rosiglitazone medicine Variables analysis: Body mass index (BMI), Insulin blood levels, Androstenedione blood levels, systolic and diastolic blood pressure and blood glucose levels. Recommended Medications: Metformin, Clomiphene and Rosiglitazone Raw Data presentation: Concluded raw data was bio-statistically represented with the application of SPSS model 2020 in which Mean Standard Deviation (Mean±SD) of different variables were considered as significant (P<0.05) variation of various regressions and concluded results were graphically showed in results.